Influence of outflow‐obstructed liver volume and venous communication development: A three‐dimensional volume study in living donors. Issue 12 (8th November 2017) - Kawaguchi, Yoshikuni; Hasegawa, Kiyoshi; Okura, Naoki; Maki, Harufumi; Akamatsu, Nobuhisa; Kaneko, Junichi; Arita, Junichi; Sakamoto, Yoshihiro; Ohtomo, Kuni; Kokudo, Norihiro
Abstract : Living donor liver transplantation using the left liver graft with the middle hepatic vein (MHV) is a well‐established procedure. Following such procedures, outflow obstruction occurs in remnant livers. However, the effects of the outflow‐obstructed liver volume (LVOut‐Ob ), with or without venous communication development, remain unclear. The aim of the study is to investigate effects of outflow‐obstructed regions by focusing on short‐term outcomes and remnant liver hypertrophy in left liver procurement donors. Of 532 donors, we collected data from 119 undergoing left liver procurement with the MHV. Postoperative hepatic parameters, venous communication development, and liver hypertrophy were evaluated in 2 donor groups based on LVOut‐Ob . The left liver was procured with the MHV in 119 donors, who formed 2 more groups based on the median LVOut‐Ob : large‐outflow‐obstruction group (n = 60; LVOut‐Ob ≥ 263 mL) and small‐outflow‐obstruction (n = 59; LVOut‐Ob < 263 mL) group. Postoperative liver function parameters were significantly impaired in the large‐outflow‐obstruction group compared with the small‐outflow‐obstruction group. Postoperative venous communication developed in 52 (66.7%) of 78 donors analyzed. Hypertrophy ratios in remnant right livers and right paramedian sectors were significantly higher in the small‐outflow‐obstruction group than in the large‐outflow‐obstruction group ( P = 0.01 and P = 0.02, respectively). The liver hypertrophy ratio of outflow‐obstructed regions was better, especially in small regions developing venous communication ( P = 0.001). The postoperative morbidity rate did not differ significantly ( P = 0.66). In conclusion, the procurement of the left liver graft with the MHV was safely performed with minimal morbidity by assessing the donor remnant right liver volume with and without outflow obstruction. Attention should be paid that postoperative hepatic parameters and remnant liver hypertrophy were impaired in the remnant livers with large outflow–obstructed regions compared with those with small outflow–obstructed regions. Liver Transplantation 23 1531–1540 2017 AASLD.